Synthesis, Characterization of Phosphate Glass Containing Silver and Antibacterial Studies of Textile Coated with Above Glass using Simple Techniques - Induja, S.; Raghavan, P.S. (Asian Journal of Chemistry, 2012)
Silver is known to kill more than 650 types of microorganisms. In order to lead a hygiene lifestyle, several attempts were made for incorporating nano particles of silver on various substrates, especially on fabric by different research groups. Nano silver with particle size less than 5 nm, invariably exist in dark yellow colour. Coating of this nano silver on fabric, impart a dirty yellow colour, which is difficult to remove, even after rigorous washing. Silver incorporated in water degradable phosphate glass matrix can be the best solution for the above said problem. In this study, the phosphate glass with varying composition with general formula (CaO)x(P2O5)y(Ag2O)z; SiO2, B2O3 were prepared, by mixing corresponding raw materials and melting between 900 ºC and 1000 ºC. The glass samples were characterized using XRD, FTIR and SEM techniques. The influence of silica and borate contents on solubility of the glass is studied in detail. Different coating techniques were adopted for coating silver on the textile and antibacterial activity studies were carried out for gram positive and gram negative bacteria, using ASTM-E-2149 procedure. Unlike nano colloidal silver, the silver-coated textile using present glass sample retained its original colour.